Peptides-Based Vaccine MP3RT Induced Protective Immunity Against Mycobacterium Tuberculosis Infection in a Humanized Mouse Model - Gong, Wenping; Liang, Yan; Mi, Jie; Jia, Zaixing; Xue, Yong; Wang, Jie; Wang, Lan; Zhou, Yusen; Sun, Shihui; Wu, Xueqiong (Frontiers in Immunology, 2021)
Background: Tuberculosis (TB) is still a global infectious disease that seriously threatens human beings. The only licensed TB vaccine Bacille Calmette-Guérin (BCG) 's protective efficacy varies significantly among populations and regions. It is very urgent to develop more effective vaccines. Methods: In this study, eleven candidate proteins of Mycobacterium tuberculosis were selected to predict peptides with high-affinity binding capacity for the HLA-DRB1*01:01 molecule. The immunodominant peptides were identified with the enzyme-linked immunospot assay (ELISPOT) and linked in silico to result in a novel polypeptide vaccine in Escherichia coli cells. The vaccine's protective efficacy was evaluated in humanized and wild-type C57BL/6 mice. The potential immune protective mechanisms were explored with Enzyme-linked Immunosorbent Assay (ELISA), flow cytometry, and ELISPOT. Results: Six immunodominant peptides screened from 50 predicted peptides were used to construct a new polypeptide vaccine named MP3RT. After challenge with M. tuberculosis, the colony-forming units (CFUs), lung lesion area, and the number of inflammatory cells in humanized mice rather than wild-type mice vaccinated with MP3RT were significantly lower than these in mice immunized with PBS. The humanized mice vaccinated with MP3RT revealed significant increases in IFN-γ cytokine production, IFN-γ+ T lymphocytes, CD3+IFN-γ+ T lymphocytes, and the MP3RT-specific IgG antibody. Conclusions: Taken together, MP3RT is a promising peptides-based TB vaccine characterized by inducing high levels of IFN-γ and CD3+IFN-γ+ T lymphocytes in humanized mice. These new findings will lay a foundation for the development of peptides-based vaccines against TB.